Isolates from hospital environments are the most virulent of the Candida parapsilosis complex - Sabino, Raquel (2011)
Background: Candida parapsilosis is frequently isolated from hospital environments, like air and surfaces, and causes serious nosocomial infections. Molecular studies provided evidence of great genetic diversity within the C. parapsilosis species complex but, despite their growing importance as pathogens, little is known about their potential to cause disease, particularly their interactions with phagocytes. In this study, clinical and environmental C. parapsilosis isolates, and strains of the related species C. orthopsilosis and C. metapsilosis were assayed for their ability to induce macrophage cytotocixity and secretion of the pro-inflammatory cytokine TNF-a, to produce pseudo-hyphae and to secrete hydrolytic enzymes. Results: Environmental C. parapsilosis isolates caused a statistically significant (p = 0.0002) higher cell damage compared with the clinical strains, while C. orthopsilosis and C. metapsilosis were less cytotoxic. On the other hand, clinical isolates induced a higher TNF-a production compared with environmental strains (p < 0.0001). Whereas the amount of TNF-a produced in response to C. orthopsilosis strains was similar to the obtained with C. parapsilosis environmental isolates, it was lower for C. metapsilosis strains. No correlation between pseudo-hyphae formation or proteolytic enzymes secretion and macrophage death was detected (p > 0.05). However, a positive correlation between pseudo-hyphae formation and TNF-a secretion was observed (p = 0.0119). Conclusions: We show that environmental C. parapsilosis strains are more resistant to phagocytic host defences than bloodstream isolates, being potentially more deleterious in the course of infection than strains from a clinical source. Thus, active environmental surveillance and application of strict cleaning procedures should be implemented in order to prevent cross-infection and hospital outbreaks.